Emissions of methane from northern peatlands: a review of management impacts and implications for future management options. Issue 19 (13th September 2016) - Abdalla, Mohamed; Hastings, Astley; Truu, Jaak; Espenberg, Mikk; Mander, Ülo; Smith, Pete
Abstract: Northern peatlands constitute a significant source of atmospheric methane (CH4 ). However, management of undisturbed peatlands, as well as the restoration of disturbed peatlands, will alter the exchange of CH4 with the atmosphere. The aim of this systematic review and meta‐analysis was to collate and analyze published studies to improve our understanding of the factors that control CH4 emissions and the impacts of management on the gas flux from northern (latitude 40° to 70°N) peatlands. The analysis includes a total of 87 studies reporting measurements of CH4 emissions taken at 186 sites covering different countries, peatland types, and management systems. Results show that CH4 emissions from natural northern peatlands are highly variable with a 95% CI of 7.6–15.7 g C m −2  year −1 for the mean and 3.3–6.3 g C m −2  year −1 for the median. The overall annual average (mean ±  SD ) is 12 ± 21 g C m −2  year −1 with the highest emissions from fen ecosystems. Methane emissions from natural peatlands are mainly controlled by water table (WT) depth, plant community composition, and soil pH. Although mean annual air temperature is not a good predictor of CH4 emissions by itself, the interaction between temperature, plant community cover, WT depth, and soil pH is important. According to short‐term forecasts of climate change, these complex interactions will be the main determinant of CH4 emissions from northern peatlands. Drainage significantly ( p  < .05) reduces CH4 emissions to the atmosphere, on average by 84%. Restoration of drained peatlands by rewetting or vegetation/rewetting increases CH4 emissions on average by 46% compared to the original premanagement CH4 fluxes. However, to fully evaluate the net effect of management practice on the greenhouse gas balance from high latitude peatlands, both net ecosystem exchange (NEE) and carbon exports need to be considered. Abstract : CH4 emissions from natural northern peatlands are highly variable with a 95% CI of 7.6–15.7 g C m −2  year −1 for the mean and 3.3–6.3 g C m −2  year −1 for the median. Drainage significantly ( p  < .05) reduces CH4 emissions to the atmosphere, on average by 84%. Methane emissions are mainly controlled by water table (WT) depth, plant community composition, and soil pH. Temperature is not a good predictor of CH4 emissions by itself, but the interaction between temperature, plant community cover, WT depth, and soil pH is important.